Merits and demerits of importing exotic cattle compared with the improvement of local breeds: Cattle in Africa South of the Sahara - Trail, J.C.M. (Cambridge University Press, 1981)
The limited genetic potential of indigenous cattle has often been quoted as a major constraint to beef and milk production in Africa south of the Sahara. Thus, considerable efforts have been and are being made to increase output through breeding programmes in many countries of the continent. These efforts include both the introduction of cattle from America, Asia and Europe for use in upgrading and crossbreeding schemes and maintenance as purebreds and the operation of selection programmes within indigenous cattle populations.